Ambulatory electrocardiography in squash players. Issue 4 (October 1983) - Northcote, R J; MacFarlane, P; Ballantyne, D
Abstract : Ambulatory electrocardiography was carried out in 21 healthy, fit, male squash players (aged 23-43 years) before, during, and after match play. Resulting electrocardiograms were analysed with respect to heart rate and changes in rhythm. The results indicate that squash increases the heart rate to 80% of an individual's predicted maximum heart rate for the duration of a game. Ventricular arrhythmias were detected in seven of the subjects during play and in seven in the immediate post-exercise period, an incidence which was not reproduced on subsequent maximal treadmill exercise testing. This study indicates that squash is a physiologically demanding sport which places a severe strain on the myocardium for considerable periods of time and is capable of generating cardiac arrhythmias. These findings are particularly important for an individual already at risk of sudden death from coronary artery disease or structural cardiovascular abnormalities. Medical advice before participation in the game will identify those at high risk of cardiovascular disease. Subjects in this study who developed arrhythmias were not, however, identified by history, examination, or exercise electrocardiography. Thus, it seems unwise to begin playing squash after the age of 40 years. Whether subjects in this age group already participating in the game should continue to play remains a matter for individual judgment.